(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
BACKGROUND:Hyponatremia is a condition when serum sodium is <135 and is considered severe when<120 mEq/L. It can be due to abnormal sodium or water balance.It is the most common electrolyte disorder occurring in critically ill patients1.Symptoms range from nausea and malaise, with mild reduction in sodium, to lethargy, decreased level of consciousness, headache and if severe seizures and coma.Aims: This retrospective study was carried to find out the epidemiology, aetiology and clinical symptoms and outcome in critically ill patients admitted with hyponatremia in intensive care unit.Method: Patients with head injury, post-operative patients, patient on renal replacement therapy and age less than 18 years were excluded.Results: Hyponatremia is common in elderly male. Drowsiness is the commonest [45%] symptoms. most common type of hyponatremia is euvolemic hyponatremia [58%]. SIADH is the commonest cause of hyponatremia followed by sepsis [15%].Conclusion: Hyponatremia is common in elderly male. Severity of hyponatremia increases as the age advances. Drowsiness is the commonest symptoms. Seizures are present only in severe hyponatremia. Overall, commonest cause of hyponatremia is SIADH.